2020
DOI: 10.1002/admi.202000425
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Garnet Li7La3Zr2O12 Electrolyte for All‐Solid‐State Batteries: Closing the Gap between Bulk and Thin Film Li‐Ion Conductivities

Abstract: The high ionic conductivity and wide electrochemical stability of the lithium garnet Li7La3Zr2O12 (LLZO) make it a viable solid electrolyte for all‐solid‐state lithium batteries with superior capacity and power densities. Contrary to common ceramic processing routes of bulk pellets, thin film solid electrolytes could enable large‐area fabrication, and increase energy and power densities by reducing the bulkiness, weight and critically, the area‐specific resistance of the electrolyte. Fabrication of LLZO films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 55 publications
1
46
0
Order By: Relevance
“…At lower LLZO:Li 2 O mass fractions, the ionic conductivity decreases again although not as abruptly as in the low Li 2 O fraction region. In contrast, the electronic conductivity remains fairly constant at 1 × 10 −14 S cm −1 for different mass fractions of LLZOand Li 2 O, seven orders of magnitude below the best ionic conductivity measured and about six orders of magnitude below reported values for bulk and thin-film crystalline LLZO 8,17.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…At lower LLZO:Li 2 O mass fractions, the ionic conductivity decreases again although not as abruptly as in the low Li 2 O fraction region. In contrast, the electronic conductivity remains fairly constant at 1 × 10 −14 S cm −1 for different mass fractions of LLZOand Li 2 O, seven orders of magnitude below the best ionic conductivity measured and about six orders of magnitude below reported values for bulk and thin-film crystalline LLZO 8,17.…”
mentioning
confidence: 58%
“…In this way it is possible to prepare ultrathin conformal and grain-boundary free films that can act as injection barrier for electrons while allowing LLZO thin films,. 16,17 Besides compensating lithium losses, it is an effective way to tune the Li-ion concentration in the electrolyte film and modify its electrochemical properties.…”
mentioning
confidence: 99%
“…While the deposition of stoichiometric crystalline LLZO by co‐sputtering of Li 2 O and LLZO was recently reported, [140] high temperatures PLD depositions still present difficulties. The presence of heavy elements, like Zr and La, leads to a significant lithium deficiency and stabilization of the La 2 Zr 2 O 7 pyrochlore phase.…”
Section: Electrolyte Materialsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Furthermore, Li-ion conductive ceramics, e.g. Li 7 La 3 Zr 2 O 12 (LLZO) [8][9][10][11] or Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 (LATP), 12,13 and glassy lithium phosphorus oxynitrides (LIPON) 14,15 form a stable solid electrolyte interface (SEI) or have a higher potential window up to 5 V vs. Li/Li + , so that less degradation of the electrolyte is expected and the implementation of high-voltage active materials might be feasible. [16][17][18] Li et al demonstrated, for instance, a highvoltage LiMn 1.5 Ni 0.5 O 4 TF-SSB using a LIPON electrolyte with a capacity retention of 90.6% after 10 000 cycles and a coulombic efficiency of almost 100%.…”
Section: Introductionmentioning
confidence: 99%